Modeling Human Cancer-induced Cachexia - Talbert, Erin E. (Cell Rep, 2019)
Cachexia is a wasting syndrome characterized by pronounced skeletal muscle loss. In cancer, cachexia is associated with increased morbidity and mortality and decreased treatment tolerance. Although advances have been made in understanding the mechanisms of cachexia, translating these advances to the clinic has been challenging. One reason for this short-coming may be the current animal models, which fail to fully recapitulate the etiology of human cancer-induced tissue wasting. Because pancreatic ductal adenocarcinoma (PDA) presents with a high incidence of cachexia, we engineered a mouse model of PDA that we named KPP. KPP mice, similar to PDA patients, progressively lose skeletal and adipose mass as a consequence of their tumors. In addition, KPP muscles exhibit a similar gene ontology as cachectic patients. We envision that the KPP model will be a useful resource for advancing our mechanistic understanding and ability to treat cancer cachexia.